2004
DOI: 10.1111/j.1463-1318.2004.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial bowel sphincter in severe anal incontinence

Abstract: Our findings indicate that the ACTICON artificial anal sphincter is well tolerated and can be an effective alternative in the treatment of severe anal incontinence. Although complete continence is only achieved in a low percentage of cases, for the rest of the patients the ACTICON neosphincter reduces the symptoms considerably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 14 publications
0
21
1
2
Order By: Relevance
“…The clinical application of AAS has been studied by many experts, and this paper summarizes and analyzes the most important 24 studies from 1996 to 2010 (Lehur et al, 1996;2000;Wong et al, 1996;Vaizey et al, 1998;Christiansen et al, 1999;Dodi et al, 2000;Malouf et al, 2000;O'Brien and Skinner, 2000;Altomare et al, 2001;2004;Devesa et al, 2002;Ortiz et al, 2002;Michot et al, 2003;Parker et al, 2003;Romano et al, 2003;Casal et al, 2004;O'Brien et al, 2004;Ruiz Carmona et al, 2009;Gallas et al, 2009;Meurette et al, 2009;Chittawatanarat et al, 2010). These studies focused chiefly on results from the clinical application of the AMS series sphincter (the unmodified AMS800, the modified version of the AMS800, and the final version, the Acticon Neosphincter) from the point of view of safety and efficacy.…”
Section: Results Of the Clinical Application Of The Ams Series Sphinctermentioning
confidence: 99%
See 4 more Smart Citations
“…The clinical application of AAS has been studied by many experts, and this paper summarizes and analyzes the most important 24 studies from 1996 to 2010 (Lehur et al, 1996;2000;Wong et al, 1996;Vaizey et al, 1998;Christiansen et al, 1999;Dodi et al, 2000;Malouf et al, 2000;O'Brien and Skinner, 2000;Altomare et al, 2001;2004;Devesa et al, 2002;Ortiz et al, 2002;Michot et al, 2003;Parker et al, 2003;Romano et al, 2003;Casal et al, 2004;O'Brien et al, 2004;Ruiz Carmona et al, 2009;Gallas et al, 2009;Meurette et al, 2009;Chittawatanarat et al, 2010). These studies focused chiefly on results from the clinical application of the AMS series sphincter (the unmodified AMS800, the modified version of the AMS800, and the final version, the Acticon Neosphincter) from the point of view of safety and efficacy.…”
Section: Results Of the Clinical Application Of The Ams Series Sphinctermentioning
confidence: 99%
“…Seventeen papers (Lehur et al, 1996;2000;Wong et al, 1996;Vaizey et al, 1998;Christiansen et al, 1999;Dodi et al, 2000;Malouf et al, 2000;O'Brien and Skinner, 2000;Altomare et al, 2001;Devesa et al, 2002;Ortiz et al, 2002;Parker et al, 2003;Casal et al, 2004;Ruiz Carmona et al, 2009;Chittawatanarat et al, 2010) reported the infection rate, which varied between 4% (Lehur et al, 2000) and 50% (Chittawatanarat et al, 2010). In three papers of Lehur et al (1996;2000), the frequencies of infection were 15%, 8%, and 4%, respectively.…”
Section: Infectionmentioning
confidence: 99%
See 3 more Smart Citations